Design, analysis and fabrication of mini soil separator machine for home gardener - Shahrul Afzam, Muhammad Nabil (2025)
This project focuses on the design and development of an innovative soil separator for small gardeners. Soil with a lot of impurities will make it difficult for plants to grow well. The soil separator plays an important role in separating the impurities such as stone, dried leaves and root. Current soil separators often suffer from inefficiencies, inconvenience, and high energy consumption. These problems will affect the soil and make gardeners' work time to be much longer, necessitating the need for advanced solutions. The purpose for this project is to minimize all the problems and develop an advanced soil separator to overcome the limitation of current models. This machine combining motor and mechanical screening to make a better soil separator than the current product. This will hugely help to separate the impurities more easily and conveniently. By applying sensors in this soil separator, real-time monitoring and control of the soil separator will be corporate. Successful implementation of the soil separator is expected to achieve environmental sustainability and improving resources efficiency.